Venture Capital Strategies as Mediating Effects in Managing the Musharakah Contract for Islamic Banking: Malaysian Demand-side Perspectives - Siti Nor Amira Mohamad; Noor Aznaim Abd Latib; Nadiah Ramlan; Siti Sarah Izham; Mohamad Yazis Ali Basah (Human Resource Management Academic Research Society, 2024)
Vol. 13, No. 2, 2023, Pg. 191 – 207